Does an incremental approach to implementing programmatic assessment work? Reflections on the change process - Bate, F.; Fyfe, Sue; Griffith, D.; Russell, Kylie; Skinner, Chris; Ng, Elina (2020)
In 2017, the School of Medicine (Fremantle) of the University of Notre Dame Australia began moving towards programmatic assessment. Programmatic assessment seeks to achieve robust assessment validity through the assessment of a large number of low-stakes activities or data points. These data points exemplify assessment as learning by valuing feedback, discussion and reflection, ultimately leading to deeper student engagement without compromising credible decision-making on student progress. The School adopted an incremental approach to implementing programmatic assessment that included first establishing data-informed mentoring, and then activating a continuous assessment program that contributed simultaneously to student learning and School decision-making. Action research helped understand the impact of the initiative. Re-engineering continuous assessment as an incremental step towards programmatic assessment proved to be problematic. Some ideas are proposed to draw the strands of programmatic assessment together that may be useful for others to chart a more fruitful path.